MOCVD-derived multilayer Gd0.5Y0.5Ba2Cu3O7−δ films based on a novel heating method. (29th December 2016) - Zhao, Ruipeng; Zhang, Fei; Liu, Qing; Xia, Yudong; Lu, Yuming; Cai, Chuanbing; Xiong, Jie; Tao, Bowan; Li, Yanrong
Abstract: Multilayer Gd0.5 Y0.5 Ba2 Cu3 O7− δ (GdYBCO) films have been deposited by the metal organic chemical vapor deposition process on LaMnO3 /epitaxial MgO/ion beam assisted deposition (IBAD)-MgO/solution deposition planarization-Y2 O3 -buffered Hastelloy tapes. The buffered tapes were heated by the Joule effect after applying a heating current ( I h ) through the Hastelloy metal substrates. For this kind of current heating method, the heating energy is transmitted from the Hastelloy metal substrate to the oxide buffer layers, thereby the surface temperature of the tape will decline with an increase in the thickness of the deposited GdYBCO film if the heating current is unchanged. Therefore, the multilayer GdYBCO film structure where I h was adjusted for each layer was adopted to make sure that the surface temperature was always high enough to deposit purely c -axis oriented GdYBCO films. With this method, four-layer 1000 nm thick GdYBCO films were successfully prepared and the critical current ( I c ) reached 328 A cm −1 width (77 K, 0 T), corresponding to the critical current density ( J c ) of 3.28 MA cm −2 (77 K, 0 T).